Infección del tracto urinario en pacientes hospitalizados con diabetes tipo 2 (2016)
Background: Urinary tract infection is more common among diabetic patients. Aim: To describe the frequency and features of urinary tract infection among diabetic patients admitted to a medicine service in Colombia. Material and Methods: Review of a database of diabetic patients aged over 18 years, admitted to a Medicine Service in Colombia. The medical records and hospital evolution of those with urinary tract infections were reviewed. Results: Data from 470 patients aged 65 ± 13 years (50% females) were reviewed. Urinary tract infections were detected in 68 (14%), all community acquired. A culture was done in 50 (73%), which was positive in 80%. The most common microorganisms isolated were Escherichia coli and Klebsiella pneumoniae in 52 and 18% respectively. Twenty eight percent of E Coli strains were resistant to extended spectrum beta lactamases and 14% of K pneumoniae strains were resistant to ampicillin. Complications were observed in 28% of these patients and 6% died, mainly due to septic shock. Glycosylated hemoglobin levels in patients with and without urinary tract infection were 9.2 and 8.5% respectively (p = 0.016). Conclusions: Urinary tract infection is common among hospitalized diabetic patients and associated with complications and higher mortality